2010
DOI: 10.4319/lo.2010.55.2.0817
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of metabolism and net heterotrophy in contrasting lakes

Abstract: We investigated the influence of light, nutrients, and organic matter on gross primary production (GPP), ecosystem respiration (R), and net ecosystem production (NEP = GPP ‐ R) in a dystrophic forest lake and an open eutrophic lake. Forest vegetation reduced incoming irradiance (20%) and wind speed (34%) in dystrophic Gribsø, having thermal stratification 1 month longer than in eutrophic Slotssø. While Gribsø had nutrient‐limited phytoplankton during most of the year, Slotssø only experienced nutrient depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 42 publications
3
64
1
Order By: Relevance
“…The environmental variables identified as drivers of planktonic metabolism in the present study (T, irradiance, phosphorus, ammonium, DOC and DO), are in general agreement with those reported in the literature for other freshwater systems (del Giorgio & Peters 1994, Cole et al 2000, Kalff 2002, Smith & Prairie 2004, Staehr et al 2010. Our study also stresses the importance of obtaining winter metabolism measurements to account for the full annual cycle, and sheds light on the complex interaction between physical and biological processes taking place in highly seasonal temperate lakes (Mortazavi et al 2001).…”
Section: Physical Chemical and Biological Controls On Lake Metabolismsupporting
confidence: 91%
See 2 more Smart Citations
“…The environmental variables identified as drivers of planktonic metabolism in the present study (T, irradiance, phosphorus, ammonium, DOC and DO), are in general agreement with those reported in the literature for other freshwater systems (del Giorgio & Peters 1994, Cole et al 2000, Kalff 2002, Smith & Prairie 2004, Staehr et al 2010. Our study also stresses the importance of obtaining winter metabolism measurements to account for the full annual cycle, and sheds light on the complex interaction between physical and biological processes taking place in highly seasonal temperate lakes (Mortazavi et al 2001).…”
Section: Physical Chemical and Biological Controls On Lake Metabolismsupporting
confidence: 91%
“…The greatest GPP:R ratios were observed during breakdown of summer stratification. This result is contrary to 2 earlier studies that concluded stratification breakdown results in reoxygenation of the hypolimnion, and the accumulated reduced substances (including CDOM) are reoxidized, resulting in increased R and reduced GPP:R values for a short period of time (Staehr & Sand-Jensen 2007, Staehr et al 2010. Other studies have reported that mixing reduces GPP due to increased turbidity through resuspended sediments and decreased light penetration (Reynolds 2010).…”
Section: Physical Chemical and Biological Controls On Lake Metabolismcontrasting
confidence: 68%
See 1 more Smart Citation
“…Despite the importance of Z mix , previous studies have often used discrete weekly temperature profiles to assess mixing depth (Lauster et al 2006; Van de Bogert et al 2007;Coloso et al 2008), although the use of high-frequency temperature profiles is increasing (Staehr and SandJensen 2007;Hanson et al 2008;Staehr et al 2010). Weekly estimates of Z mix are interpolated to daily or subdaily time series for use in a model to estimate daily rates of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Correcting for autocorrelation in regression models has been used in the statistics and economics fields for decades (e.g., Durbin 1960, Beach andMacKinnon 1978), but has gained increasing use in ecological studies in recent years (e.g., Carpenter et al 1998, Lichstein et al 2002, Staehr et al 2010b …”
Section: Long Term Hydrologic and Water Quality Variablesmentioning
confidence: 99%